Socio-economically challenged learners: two South African case studies - Moloi, Connie; Kamper, Gerrit (University of the Free State, 2010)
This article reports the results of research conducted in two successful secondary schools situated in a poor rural area in the Ehlanzeni region, Mpumalanga province. The research forms part of the International Successful School Principals Project (ISSPP) which originated in 2001 among a group of experienced education leadership and management researchers. Notwithstanding a comprehensive body of research data on the qualities of good principalship and successful schools, there was a need to focus more directly on how to create and sustain a supportive teaching and learning environment for socio-economically challenged learners.

Hierdie artikel handel oor navorsing in twee suksesvolle sekondêre skole wat geleë is in die verarmde platteland van die gebied Ehlanzeni in Mpumalanga. Die navorsing is deel van die International Successful School Principals Project (ISSPP) wat in 2001 deur ’n aantal deskundige navorsers in onderwysleierskap en -bestuur geïnisieer is. Met inagneming van die beskikbaarheid van omvangryke data oor die kenmerke van suksesvolle skole en skoolhoofde fokus die navorsing meer op hoe om ’n ondersteunende onderrig- en leeromgewing vir sosio-ekonomies benadeelde leerders te skep en te volhou
Keywords: Ehlanzeni region, Mpumalanga; International Successful School Principals Project